Factors Influencing Customer Experience and Satisfaction in E-hailing Services: A Case Study of GrabCar - Jamin Kun Peng Xia; Louis Yong Yu Lee; Dwi Nita Aryani; Yu Xuan Cheah; Yu Xuan Chee; Wen Hui Cheang; Yiming Chen; Virly Assa Lunsa; Suresh Poddar; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2025)
E-hailing has become an increasingly popular mode of transportation in Southeast Asia, with GrabCar being one of the leading platforms offering convenient and affordable mobility solutions. This study aims to investigate the factors influencing customer experience and satisfaction in using GrabCar services. The independent variables include perceived ease of use, perceived fare, perceived trust, perceived risk, and perceived convenience, with customer experience serving as a mediating variable and customer satisfaction as the dependent variable. A quantitative method was applied through a structured questionnaire distributed to 150 respondents from Malaysia, Indonesia, and India, and the data were analyzed using SPSS. The regression results show that customer experience is significantly influenced by perceived ease of use (? = 0.221, p .001), perceived fare (? = 0.174, p .01), and perceived risk (? = 0.423, p .001), while customer satisfaction is affected by perceived fare (? = 0.341, p .001), perceived convenience (? = 0.251, p .001), and customer experience (? = 0.407, p .001). GrabCar should prioritize fair pricing, user-friendly design, safety, and convenience to enhance experience and satisfaction.